A NEW SOLVENCY PREDICTION MODEL FOR COMPANIES IN THE REAL ESTATE SECTOR - Perim, Pablo Pulhese; Monte-Mor, Danilo Soares; Sanfins, Marco Aurélio dos Santos; Tardin, Neyla (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study aims to propose a model that estimates insolvency risk for real estate companies through an approach that considers, in addition to the assets' quality, the mismatches between assets and liabilities on time, as well as different risks within the sector. Through Monte Carlo simulations and hypothetical examples, we show that the proposed model was able to capture mismatches between assets and liabilities and the effects of changes in the risks of credit, liquidity and engineering. In addition, our results suggest that the absence of a harmonious distribution of assets and liabilities leads to increasing insolvency risks even when the present value of total assets is greater than the present value of total liabilities.